1995
DOI: 10.1128/aem.61.10.3592-3597.1995
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose and sucrose protect both membranes and proteins in intact bacteria during drying

Abstract: The microorganisms Escherichia coli DH5␣ and Bacillus thuringiensis HD-1 show an increased tolerance to freeze-drying when dried in the presence of the disaccharides trehalose and sucrose. When the bacteria were dried with 100 mM trehalose, 70% of the E. coli and 57% of the B. thuringiensis organisms survived, compared with 56 and 44%, respectively, when they were dried with sucrose. Only 8% of the E. coli and 14% of the B. thuringiensis organisms survived drying without the sugars. Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
431
0
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 844 publications
(467 citation statements)
references
References 34 publications
20
431
0
16
Order By: Relevance
“…The charged sugars were then eluted with a 0-0.3 M linear gradient of NH 4 HCO 3. As shown in profile A, a sharp symmetrical peak of radioactivity emerged at 0.1-0.15 M NH 4 HCO 3 and fractions [23][24][25][26][27][28][29][30][31][32] containing radioactivity were pooled and concentrated several times with triethylamine to remove the NH 4 HCO 3 . In profile B, the charged compound was treated with alkaline phosphatase and subjected to paper chromatography in solvent A.…”
Section: Discussionmentioning
confidence: 99%
“…The charged sugars were then eluted with a 0-0.3 M linear gradient of NH 4 HCO 3. As shown in profile A, a sharp symmetrical peak of radioactivity emerged at 0.1-0.15 M NH 4 HCO 3 and fractions [23][24][25][26][27][28][29][30][31][32] containing radioactivity were pooled and concentrated several times with triethylamine to remove the NH 4 HCO 3 . In profile B, the charged compound was treated with alkaline phosphatase and subjected to paper chromatography in solvent A.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 It has been conclusively demonstrated that sugars (e.g., sucrose, trehalose) are able to preserve macromolecules during drying. 17 The mechanism by which sugars exert their protective effect is thought to involve both glass formation 18,19 and hydrogen bonding, 20 although the validity of these mechanisms is still debated. 21 Regardless of the precise mechanism responsible for stabilization, the role of water as both a reactant and plasticizer suggests that progressively greater stability should be observed at lower moisture contents.…”
Section: Introductionmentioning
confidence: 99%
“…Compatible solutes consist of sugars, polyols, amino acids and derivatives thereof. They stabilize cellular structures and restore the osmotic balance without interfering with the functioning of biomolecules (Leslie et al, 1995;Shen et al, 1999;Billi et al, 2000). Protective proteins bind to and structurally stabilize other proteins, membranes and RNA (Warner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%